Low Social Support at Work and Ambulatory Blood Pressure in a Repeated Cross-sectional Study of White-Collar Workers. Issue 3 (11th November 2021) - Trudel, Xavier; Tiwa Diffo, Edwige; Gilbert-Ouimet, Mahée; Mésidor, Miceline; Talbot, Denis; Milot, Alain; Brisson, Chantal
Abstract: Objectives: Previous studies on the effect of low social support at work on blood pressure showed mixed results. Few previous studies have used ambulatory blood pressure and examined whether the effect of low social support at work vary among men and women. The aim of this study was to examine the association between low social support at work, ambulatory blood pressure means and hypertension prevalence, in a sample of white-collar workers men and women. Methods: A repeated cross-sectional design was used. Data were collected three times during a 5-year period, among 3919 white-collar women and men. At each time, coworker and supervisor social support at work were measured using validated scales. Ambulatory blood pressure was measured every 15 min during a working day. General estimating equations were used. Results: In adjusted models, women exposed to low coworker (+0.6 mmHg) and low supervisor social support at work (+0.7 mmHg) had slightly higher diastolic blood pressure means when compared to unexposed women. In men, those with low coworker social support at work had higher diastolic (+0.7 mmHg) blood pressure while those with low supervisor social support had a higher prevalence of hypertension (prevalence ratio = 1.14, 95% CI: 1.04–1.24). Conclusions: Men with low supervisor social support at work had a higher prevalence of hypertension. Low social support at work was associated with modest increases in diastolic blood pressure among men and women. Workplace prevention strategies aiming to increase social support at work could lead to beneficial effects on worker's cardiovascular health.